Unravelling discourses about the management of a migratory declining game species: the case of European Turtle-dove (Streptopelia turtur) - Lara Moreno-Zarate; Beatriz Arroyo; Zebensui Morales-Reyes; Miguel Delibes-Mateos (Ecosystems and People)
Managing migratory game species is challenging and often leads to conflicts across areas or stakeholders. The European Turtle-dove Streptopelia turtur (TD), a declining migratory game bird, is currently subject to an adaptive harvest management plan in the European Union (EU), which has led to a temporary hunting moratorium in western Europe. We used Q-methodology to identify the discourses of hunters, hunting lobbyists and members of governmental agencies in Spain, the country with the largest TD hunting bags within EU, regarding the role of hunting and its regulation, including the moratorium, on species recovery prospects. Three discourses were identified: one that denies any involvement of hunting in the species population decline and thus considers the moratorium unnecessary; one that advocates for a moratorium but highlights the need for global strategies for it to be effective; and one that disputes the population decline, attributing the moratorium purely to environmentalists’ pressures and false data. Larger differences were observed among hunters from areas with varying levels of TD hunting than among hunters that hunt or not TD, suggesting that discourses may be socially constructed and maintained. Hunting lobbyists’ discourse was more uniformly against the moratorium than that of hunters as a whole, while governmental agencies had more nuanced perspectives. A point of consensus among discourses was the agreement on the need for transboundary coordination and a global conservation strategy incorporating habitat and hunting management approaches. These results emphasize the importance of increased transborder collaboration and effective communication strategies to mitigate conflicts about migratory game management.